Poverty in an International Perspective: A Reexamination - Orit Kristal; Leah Achdut (Luxembourg Income Study (LIS), 1993)
Poverty rankings of LIS countries given by traditional Head Count and Poverty Gap measures are compared to the rankings found using Sen (1976), Kakwani (1980), and Foster et al. (1984). It is found that the latter measures lead to more consistent rankings.
Keywords: 330